Promotion of knowledge transfer and retention in year 2 medical students using an online training exercise - Rosby, Lucy Victoria (2022)
It was recently shown that novice medical students could be trained to demonstrate the speed-to-diagnosis and diagnostic accuracy typical of System-1-type reasoning. However, the effectiveness of this training can only be fully evaluated when considering the extent to which knowledge transfer and long-term retention occur as a result, the former of which is known to be notoriously difficult to achieve. This study aimed to investigate whether knowledge learned during an online training exercise for chest X-ray diagnosis promoted either knowledge transfer or retention, or both. Second year medical students were presented with, and trained to recognise the features of four chest X-ray conditions. Subsequently, they were shown the four trained-for cases again as well as different representations of the same conditions varying in the number of common elements and asked to provide a diagnosis, to test for near-transfer (four cases) and far-transfer (four cases) of knowledge. They were also shown four completely new conditions to diagnose. Two weeks later they were asked to diagnose the 16 aforementioned cases again to assess for knowledge retention. Dependent variables were diagnostic accuracy and time-to-diagnosis. Thirty-six students volunteered. Trained-for cases were diagnosed most accurately and with most speed (mean score = 3.75/4, mean time = 4.95 s). When assessing knowledge transfer, participants were able to diagnose near-transfer cases more accurately (mean score = 2.08/4, mean time = 15.77 s) than far-transfer cases (mean score = 1.31/4, mean time = 18.80 s), which showed similar results to those conditions previously unseen (mean score = 0.72/4, mean time = 19.46 s). Retention tests showed a similar pattern but accuracy scores were lower overall. This study demonstrates that it is possible to successfully promote knowledge transfer and retention in Year 2 medical students, using an online training exercise involving diagnosis of chest X-rays, and is one of the few studies to provide evidence of actual knowledge transfer.